Design and operation of a pilot plant for biomass to liquid fuels by integrating gasification, DME synthesis and DME to gasoline. (15th December 2016) - Wang, Zhiqi; He, Tao; Li, Jianqing; Wu, Jingli; Qin, Jianguang; Liu, Guangbo; Han, Dezhi; Zi, Zhongyue; Li, Zhuo; Wu, Jinhu
Highlights: The process and performance of a pilot-scale BTL plant were presented. The feasibility of DME to gasoline in the designed facilities was demonstrated. The manipulation of reaction heat and CO conversion were evaluated and verified. The per-pass CO conversion of 45% and gasoline yield of 4.4 kg/h were achieved. Abstract: Based on a promising process of biomass to liquid (BTL) fuels, a pilot-scale plant including gasification, direct synthesis of dimethyl ether (DME) and DME to gasoline was developed. The evaluations of the designed facilities and the optimization of the operation parameters for the whole system were carried out. The several running tests demonstrated the feasibility of converting biomass to high octane gasoline in the developed pilot plant. The adopted critical components of the facilities were verified and the anticipated design goal was achieved. The operating results showed that both the pressure and gas hourly space velocity (GHSV) not only influenced the CO conversion and the DME yield, but also had a significant effect on the manipulation of the reaction heat in the adiabatic reactor. High pressure and low GHSV favored the high CO conversion and the DME yield. Considering CO conversion and temperature controlling of the adiabatic reactor, the optimized pressure and GHSV of the synthesis process were 2.2–2.5 MPa and 1200 h −1, respectively. The per-pass conversion of CO and the production capacity of gasoline were about 45% and 4.4 kg/h, respectively under this condition.